A systematic review and meta‐analysis of lifestyle interventions in women of reproductive age with overweight or obesity: the effects on symptoms of depression and anxiety. (28th August 2018) - van Dammen, L.; Wekker, V.; de Rooij, S. R.; Groen, H.; Hoek, A.; Roseboom, T. J.
Summary: Obesity is a rising problem, especially among women of reproductive age. Overweight and obesity reduce both physical and mental health. Lifestyle interventions could have beneficial effects on both, but an overview of the effects on mental health, especially in women of reproductive age, is currently lacking. Therefore, the aim of this review was to assess the effect of lifestyle interventions on symptoms of depression and anxiety in women of reproductive age with overweight or obesity. The databases MEDLINE, EMBASE and PsycINFO were searched from inception to June 2018 for published randomized controlled trials (RCTs). We included lifestyle intervention RCTs in women of reproductive age with overweight or obesity that assessed effects on symptoms of depression and/or anxiety. The difference between baseline and post‐intervention scores on symptoms of depression and anxiety for the intervention and control group was analysed. Meta‐analysis was performed with a random effects model.* The search resulted in 5, 316 citations, and after screening five RCTs were included, in which 571 women were randomized. The effect of lifestyle interventions on depression scores was investigated among 224 women from five RCTs. The pooled estimate for the mean difference was −1.35 (95% CI, −2.36 to −0.35, p  = 0.008). The effect of lifestyle interventions on anxiety levels was studied among 148 women from four RCTs, resulting in a pooled estimate of −1.74 (−2.62 to −0.87, p  < 0.001). Based on five RCTs, meta‐analyses showed that lifestyle interventions in women of reproductive age with overweight or obesity consistently reduce symptoms of depression and anxiety.